Building Bridges: The Erasmus+ Project of the Castilla-La Mancha Inspectorate as a Tool for Internationalising Educational Supervision - Moratalla Isasi, Silvia; Gutiérrez Martínez, Victor Manuel (Avances en Supervisión Educativa, 2026)
This article presents the Building Bridges project (KA122-ADU-8890EA10), the first Erasmus+ initiative led directly by the Education Inspectorate of Castilla-La Mancha in the field of adult education. The project, funded with 42,588 euros through SEPIE (2025 call), will mobilise 30 participants across seven countries over 16 months. Empirical results from the first three job shadowing mobilities carried out in Madeira (Portugal), Brussels (Belgium) and Basilicata (Italy) are presented. Findings reveal advanced European models of flexible learning, prior learning recognition, non-formal vocational training and teacher evaluation. Transferable practices to the Castilla-La Mancha context are identified, and the role of the inspectorate as an active internationalisation agent is examined, in the framework of the debate held at the ADIDE Madrid Conference in November 2025.